Effect of two ram sperm capacitating media on acrosome reaction and zona-free hamster oocyte penetration test - Ferrari, Silvia; Barnabe, Valquíria Hyppolito; Züge, Roberta Mara; Zogno, Maria Amélia (Brazilian Journal of Veterinary Research and Animal Science, 2000)
An in vitro zona-free hamster oocyte penetration test was utilized in 24 trials in order to evaluate the capacitation media used for ram sperm. A pool of fresh semen was collected from three crossed breed rams. Two semen drops were washed by centrifugation and incubated in high ionic strength treatment (HIS) or in a defined medium with HEPES, on heat ewe serum and heparin. After the incubation to promote capacitation, simplified triple-stain technique was used to evaluate the spontaneous acrosome reaction of the capacitated sperm. Superovulation in 96 golden hamsters was induced by PMSG and hCG. The oocytes were treated with hyaluronidase and trypsin to remove, respectively, the cumulus cells and the zona pellucida. Oocytes and capacitated sperm were incubated during 3 hours for further penetration. Then, oocytes were fixed and stained, being evaluated under phase contrast microscope. No significant statistical difference (p >; 0.05) was found between media, concerning the penetration rate of the capacitated sperm and between number of sperm viable with acrosome reaction after the capacitation treatment using two different media. It was concluded that both media utilized were effective in capacitating ram sperm.